2020
DOI: 10.7759/cureus.6604
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Cost-Effective Pediatric Intubation Task Trainer for Rural Medical Education

Abstract: Pediatric intubation and airway management (PIAM) is a life-saving, emergent procedure that is performed by a variety of healthcare practitioners. Securing the pediatric airway in a timesensitive fashion is a specialized skill that declines with lack of practice, leading to a precarious gap in clinical competency and healthcare delivery. However, current training models for PIAM, such as live animals, human cadavers, and simulators, are not adequately accessible or reliable due to their combination of high cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Eight studies used 3D-printed models for preoperative planning and simulation of airway management in complex cases, five of which were in children. 1724 Kavanagh and colleagues developed four models using 3D printing, including three direct-printed models made with different materials, including polylactic acid (PLA), acrylonitrile butadiene styrene and high-impact polystyrene, and a silicone model made from a 3D-printed cast. 18 These were tested by four otolaryngologists who concluded that the cast model was significantly better in terms of tissue characteristics, ease of tissue manipulation and overall accuracy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies used 3D-printed models for preoperative planning and simulation of airway management in complex cases, five of which were in children. 1724 Kavanagh and colleagues developed four models using 3D printing, including three direct-printed models made with different materials, including polylactic acid (PLA), acrylonitrile butadiene styrene and high-impact polystyrene, and a silicone model made from a 3D-printed cast. 18 These were tested by four otolaryngologists who concluded that the cast model was significantly better in terms of tissue characteristics, ease of tissue manipulation and overall accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…18 Similar findings were also observed in two other studies reporting on the development of paediatric intubation simulation models involving the 3D printing of airways using black resin and red Ninjaflex (NinjaTek, Manheim, PA, USA). 17 , 19 Challenges included that the black colour used in the resin obscured the intubating view and while Ninjaflex was most comparable to soft tissue, it did not demonstrate the same yield as human tissue. 17 , 19 Single patient case studies were reported including complex cases of intubations involving children with Jarcho–Levin syndrome 20 and another with pulmonary alveolar proteinosis requiring single-lung ventilation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtual reality simulators (Davies et al, 2013;Cagiltay et al, 2019), and full-and partial-body training simulators such as TraumaMan (Hall et al, 2014), SimMan 3G (Silverplats et al, 2016) or their low-cost alternative SurgeMan (Garcia et al, 2019), are providing the technology to aid fulfil training needs, evaluation of individual technical skills and team training on non-technical skills. 3D printing has also been implemented to create models for training, for example, cervical laminectomy or paediatric emergency procedures (Kovatch et al, 2020;Tanya and Dubrowski, 2020). These and other simulators are currently used to train surgeons to perform various routine operations in order to learn the appropriate skills for interventions on real patients (Tab.…”
Section: Human Surgical Trainingmentioning
confidence: 99%
“…On the contrary, synthetic models are good alternatives; however, they are costly, often lack realism, and do not provide the variability that is often needed for learning [4]. With the advent of additive manufacturing, such as 3D printing, we are now able to design and build inexpensive, realistic, and variable synthetic simulators [5][6][7][8]. Developing inexpensive IM injection simulations directed to nursing students will allow the aspiring nurses to become well acquainted with the skill before entering the clinical setting.…”
Section: Introductionmentioning
confidence: 99%